The patient relationship and therapeutic techniques of the South Sotho traditional healer - MG Pinkoane; M Greeff; MJS Williams (AOSIS, 2005)
Until 1996 the practice of traditional healers was outlawed in South Africa and not afforded a legal position in the community of health care providers. In 1978 the World Health Organization (WHO) identified traditional healers as those people forming an essential core of primary health care workers for rural people in the Third World Countries. However in 1994 the new South African government identified traditional healers as forming an essential element of primary health care workers. It is estimated that 80% of the black population uses traditional medicine because it is deeply rooted in their culture, which is linked to their religion. The traditional healer shares with the patient a world view which is completely alien to biomedical personnel. Therapeutic techniques typically used in traditional healing conflict with the therapeutic techniques used in biomedicine. The patients' perceptions of traditional healing, their needs and expectations, may be the driving force behind their continuous persistence to consult a traditional healer, even after these patients may have sought the therapeutic techniques of biomedical personnel. The operation of both systems in the same society creates a problem to both providers and recipients of health care. Confusion then arises and the consumer consequently chooses the services closer to her. The researcher aimed at investigating the characteristics of the relationship between the traditional healers and the patients, explored the therapeutic techniques that are used in the South Sotho traditional healing process, and investigated the views of both the traditional healers and the patients about the South -Sotho traditional healing process, to facilitate incorporation of the traditional healers in the National Health Care Delivery System. A qualitative research design was followed. Participants were identified by means of a non-probable, purposive voluntary sample. Data was collected by means of a video camera and semi-structured interviews with the six traditional healers and twelve patients, as well as by taking field notes after each session. Data analysis was achieved by means of using a checklist for the video recordings, and decoding was done for the interviews. A co-coder and the researcher analysed the data independently, after which three consensus discussions took place to finalise the analysed data. The researcher made conclusions, identified shortcomings, and made recommendations for application to nursing education, nursing research and nursing practice. The recommendations for nursing practice are reflected in the form of guidelines for the incorporation of the traditional healers in the National Health Care Delivery System.